Effectiveness of Basic Physics II Practicum Guidelines Based On Science Process Skills - Darmaji Darmaji; Dwi Agus Kurniawan; Ai Suryani (STKIP Singkawang, 2019)
The Jambi University Physics Education Study Program has developed a Basic Physics II practicum guidelines based on science process skills that valid and reliable. However, there has not been a large scale implementation to determine the effectiveness of the guidelines. The purpose of this study was to determine the mastery of student science process skills after using the Basic Physics II practicum guidelines based on science process skills on refraction subject mater. This research is a quantitative research type of pre-experimental design with the One-Shot Case Study. The research sample was the Physics Education second year students of Jambi University, amounting to 87 people. Data collection is done by observing using observation sheets about science process skills. Data were analyzed using descriptive statistics. The results showed that students were very good at mastering science process skills after using practicum guidelines based on science process skills. Percentage of mastery of science process skills for refraction practicum on parallel plan glass including: observation 64.84%; experimental planning: 64.84%; prediction 61.54%; conducting experiment 53.85%; measuring 49.45% and variabel identification 28.57%. On average, students were very good at mastering science process skills in refraction practicums in prisms with their respective percentages: planning experiments 61.54%; prediction 58.24%; observation 48.35%; conducting experiment 45.05%; measuring 39.56% and identifying variables 32.97%.